PERBANDINGAN ANALISIS STRUKTUR PELAT LANTAI BETON KONVENSIONAL DAN PELAT LANTAI HASILPERHITUNGAN SOFTWARE SAP 2000 (MENARA USM) - Ngudi Hari Crista Hari (Journal of Civil Engineering and Technology Sciences, 2022)
The floor slab is designed to behave as a diaphragm during an earthquake (Ultimate limit states). Floor slabs are designed in such a way that deflection and vibration are within serviceability limit states. The criteria for the maximum plate deflection are used according to SNI 2847-2019. The analysis carried out is to compare the work of conventional concrete floor slabs and floor slabs as a result of the output analysis from the SAP 2000 software. The goal to be achieved in this study is to analyze the structure of conventional concrete slabs with the results of computer software to obtain the difference in plate reinforcement spacing so that it will be obtained optimal distance. From the conclusions of the research that has been carried out, it is obtained that conventional concrete floor slabs are narrower than the results of the spacing of the reinforcement from the software results, for the SAP output the spacing is more tenuous. Based on these results, for the selection of reinforcement spacing, it is recommended to use the smallest spacing. obtained by Manual analysis is at moment 11 of Mu = 11.109 kNm with a diameter used for Ø 10-100 mm reinforcement, while analysis with SAP 2000 software is obtained at moment 11 for M11 = 9.876 kN.m with a diameter used for plain reinforcement Ø10-150 .Based on the plate moment obtained by Manual analysis is at moment 22 of Mu = 7.454 kNm with a diameter used for reinforcement Ø 10-150 mm, while analysis with SAP 2000 software is obtained at moment 22 of Mu = 6.507 kN.m with a diameter used plain reinforcement Ø10-200.